A study of friction behaviour and lubricant thickness effects in head disk interface - Gan, Wuxing (2009)
In hard disk drives (HDDs), lubricants are commonly accepted to be a main application to reduce the stiction and friction, protect wear and increase the reliability of magnetic storage. Unlike conventional lubrication, the experimental results have shown that the untra-thin film of organic lubricants in the micro or nano scale tribology, so called nanotribology has different friction behaviour. Various ultra thin film lubricants of disks were involved in the experiments. In all the cases friction characteristic exhibited dependence of sliding velocity. This is in contrary to the classic friction law: "the friction force is independent of velocity once motion starts, no matter how fast the relative speed between two solid bodies' interface is, friction remains nearly the same amount of resistance". Experiment data presented supports the relevant theories or discussion hypothesis.